The temporality of taste in eighteenth-century British writing - Noggle, James (Oxford : Oxford University Press, 2012)
This text discusses the disruptive power of the concept of taste in the works of a number of important British writers, including poets such as Alexander Pope and Joseph Warton, philosophical historians such as David Hume and Anna Barbauld, and novelists such as Frances Burney and William Beckford.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: English literature -- 18th century -- History and criticism; Taste in literature